Asthma and pregnancy: A review of management strategies with an emphasis on medication safety and outcomes. Issue 3 (3rd July 2018) - Conte, T.; Bergeron, C.; FitzGerald, J. M.
ABSTRACT: INTRODUCTION: Globally the prevalence of asthma during pregnancy is increasing and asthma brings a greater risk of maternal and perinatal complications including: pre-term delivery, low birth weight and birth anomalies. Appropriate management of asthma has shown to mitigate many of these adverse outcomes. This review aims to give clinicians a general overview on the epidemiology, management and safety of asthma treatment during pregnancy. METHODS: We performed a narrative literature review to offer a broad perspective of the most relevant aspects of asthma during pregnancy. RESULTS: Evidence shows that the risks of guideline-based asthma treatment are lower than the risks and outcomes associated with poorly controlled asthma, especially in regards to malformations. Asthma is not a contraindication to pregnancy and likewise most currently available treatments are not contraindicated in pregnancy. A multidisciplinary approach is the ideal strategy, with a special emphasis on increasing adherence, which will be associated with better outcomes for both the mother and baby. CONCLUSION: Asthma management during pregnancy follows the same principles as that of in the non-pregnant asthma subject but there needs to be a strong emphasis on achieving good adherence.